Build It! Volume 3 make supercool models with your LEGO classic set - Kemmeter, Jennifer (Portland, OR Graphic Arts Books, 2016)
Inside Volume 3 you'll find a range of creative models to put together--from neighborhood scenes to exotic animals to a busy airport, and much more, created using the LEGO® Classic set 10698, or bricks you already have at home. Each book in this interactive series contains 3-5 dioramas featuring a diverse range of models. Full color, step-by-step diagrams guide you through the process, enhancing the fun.
For ages 5+.
104563
Keywords: LEGO toys -- Juvenile literature; Models and modelmaking -- Juvenile literature; Juvenile works